Animal personality and pace-of-life syndromes: do fast-exploring fairy-wrens die young? - Hall, Michelle L.; van Asten, Timon; Katsis, Andrew C.; Dingemanse, Niels J.; Magrath, Michael J. L.; Mulder, Raoul A. (Frontiers in Ecology and Evolution, 2015)
The pace-of-life syndrome (POLS) hypothesis for animal personality proposes that variation among individuals in life-history strategies is associated with consistent differences in behavior. We tested predictions of this hypothesis in the superb fairy-wren, Malurus cyaneus, by investigating long-term individual differences in risk-related behaviors (latency to enter a novel artificial environment, exploration, activity and response to mirror image stimulation) and survival. We found consistent differences between individuals in these behaviors (adjusted repeatability of exploration of artificial novel environment = 0.37). Individual differences were consistent over several years and bi-variate analyses showed a significant among-individual correlation (‘behavioral syndrome’) between exploration behavior at two life stages (young adult and old adult). Docility at the nestling stage predicted exploration behavior of juveniles. Behavioral traits measured in a risky context were correlated with one another, forming a behavioral syndrome of coping strategies ranging from ‘proactive’ to ‘reactive’. Nestlings that were more active and exploratory in isolation were less docile during handling, while adults that entered the artificial environment fast were more exploratory, active, and aggressive in the artificial environment. Exploration behavior increased within individuals as they aged and when they were in poorer condition, consistent with expectations of more risk-prone behavior with lower residual reproductive value (reduced ‘asset protection’). Risk-related behavior predicted the probability of apparent survival: more exploratory individuals were less likely to be present in the population twelve months later. Our findings suggest that, consistent with the predictions of the POLS hypothesis, individual variation in survival is associated with consistent individual differences in risk-related behavior that are maintained long-term and span developmental boundaries.